Constitutional law of India - Seervai, H. M. (Bombay, 1976)
The second edition of the Constitutional Law of India was overtaken by events. The first volume was in the press when Mrs. Gandhi advised the President of India to proclaim an Emergency on the ground of "internal disturbance", and the Emergency was proclaimed on 26th June, 1975. The second volume was published in May 1976 when the Emergency was in force. The 39th Amendment, which came into force on August 10, 1975 gave a foretaste of what was to come by way of further amendments. On April 28, 1976 the Supreme Court handed down five Judgments in A.D.M. Jabalpur v. Shivkant Shukla ("The Habeas Corpus Case"). By a majority of 4:1, the Supreme Court overruled the unanimous views of 9 High Courts and held that in view of the Presiden tial Order dated 27th June 1975, no person had a locus standi to move any writ petition under Art. 226 for habeas corpus. With the Supreme Court handing over the lives and personal liberties of citizens to Mrs. Gandhi, and Mr. Justice Beg giving her a certificate that "the care and concern shown for the detenus" was "almost maternal" since "they were well housed, well-fed and well-treated", she saw the path clear before her. She struck at the High Court judiciary by executive action, and at the Supreme Court and the High Courts by the 42nd Amendment, whose other provisions took the Constitution of India towards a dictatorship.
Keywords: Constitutinal law